Examination of Fatigue, Well-Being and Life Habits in Children with Cancer Diagnosis - Sümeyye SEVGİLİ; Sedef ŞAHİN; Burcu Semin AKEL (Bezmiâlem Science, 2021)

(untitled)
Objective:In this study, it was planned to examine fatigue, well-being and life habits in children with cancer.Methods:This cross-sectional analytical study was conducted between September 2019-January 2020. “24-Hour Child Fatigue Scale”, “Child Well-being Assessment” and Child Life Habit Questionnaire (LIFE-H for Children 1.0)” were administered to 20 children with cancer aged 5-15 years. Pearson’s correlation coefficient was used to determine the statistical relationship between life habits, fatigue and well-being. Statistical significance level was accepted as p<0.05.Results:There were significant relationships between fatigue and personal care, shelter and mobility parameters of life habits (r=-0.66, r=0.54, r=0.45, p<0.01, respectively) and there were significant relationships between fatigue and negative emotions (r=0.46), overall life satisfaction (r=-0.52), general happiness (r=- 0.49) and positive emotions (r=-0.44 *) parameters of well-being assessment. Life habits scale was found to be related with nutrition, physical fitness and communication parameters of Child Life Habit Questionnaire were found to be most related with the meaning and purpose parameter of the well-being assessment (p<0.01). There were significant relationships between positive emotions and recreation (r=0.45, p=0.04); optimism and communication (r=-0.44, p=0.04); personal care (r=-0.49, p=0, 02), social life (r=-0.46, p=0.04) and autonomy; and mobility and negative emotions (r=-0.45, p=0.04).Conclusion:Considering the relationships determined in this study, the evaluation of the children with cancer and treatment approaches can be shaped. The fact that fatigue affects all aspects of children’s life reveals the importance of dealing with fatigue. It is recommended to focus on the meaning and purpose and regain autonomy for children in order to rearrange the life habits of the children and ensure their well-being.